2017
DOI: 10.1186/s41935-017-0006-x
|View full text |Cite|
|
Sign up to set email alerts
|

A medicolegal study of domestic violence in south region of Jordan

Abstract: BackgroundDomestic violence is a forced pattern of behavior that happened in domestic settings to gain or maintain power and control over an individual. The aim of this work is to study the magnitude of domestic violence in south region of Jordan.MethodsThe retrospective study was retrieved from the medico-legal reports of domestic violence cases referred to the Directorate of Forensic Medicine in south region of Jordan during six years period starting from 1st of January 2010 till the end of December 2015.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This is explained by the fact that 60% of the assailants used physical forces in the current review which might result in physical injury. The finding is similar to a medicolegal study of domestic violence in the southern region of Jordan by Hasan Al-Hawari and Asmaa El-Banna [ 20 ]. The physical findings in all five male victims who reported anal penetration were perianal lacerations with intact anal sphincter.…”
Section: Discussionsupporting
confidence: 88%
“…This is explained by the fact that 60% of the assailants used physical forces in the current review which might result in physical injury. The finding is similar to a medicolegal study of domestic violence in the southern region of Jordan by Hasan Al-Hawari and Asmaa El-Banna [ 20 ]. The physical findings in all five male victims who reported anal penetration were perianal lacerations with intact anal sphincter.…”
Section: Discussionsupporting
confidence: 88%
“… Al-Gharaibeh, Fakir [ 33 ] 2016 Debating the role of custom, religion and law in ‘honour’ crimes: implications for social work Supportive Environment SGBV - Honor Killing Twenty-four Jordanian criminal trials of perpetrators of ‘honour’ killings from 2010 to 2014 were analysed. Most victims were unmarried women or young girls who were murdered by male relatives, usually brothers, for reasons including absence from home, being raped and talking on the phone Al-Hawari, H; El-Banna, A [ 34 ] 2017 A medicolegal study of domestic violence in south region of Jordan Youth SGBV Examination of medical records after reported cases of abuse in population aged between 6 and 18 and above Young women between the ages of 12–18 were more likely than other age groups to experience sexual abuse. “illegal” pregnancy occurred in 13% of the cases.…”
Section: Resultsmentioning
confidence: 99%
“…A study that uses data from the 2012 Jordan Population and Family Health Survey (JPFHS) suggest that about 25% of married women aged 15-29 experience domestic violence, which is similar to that estimated among all women of reproductive age [45], while another study focused on SGBV during pregnancy found no differences in prevalence according to age and found that across all ages, physical, emotional, verbal and sexual violence perpetrated by husbands during their wife's pregnancies were estimated to be 10.4, 23.4, 23.7, and 5.7%, respectively. A forensic analysis of medical records of reported cases of abuse among Jordanians found that in the Southern region of Jordan young women between the ages of 12-18 were more likely than other age categories to report and seek medical attention for having experienced abuse (32.8% of the 128 cases reviewed occurred among women aged 12-18), and sexual abuse was the most common form (41.1% of all cases, but not disaggregated by age) [34]. The consequences of sexual abuse were severe: 20% of the young women left their home and 13% of the victims became pregnant with pregnancies that are considered to be illegal by the state, as they were outside of wedlock [34].…”
Section: Prevalence Of Sgbv Honor Killing and Early Marriage Among Ymentioning
confidence: 99%
See 1 more Smart Citation
“…The Regional Training Center has not only helped in building capacities of personnel who work on domestic violence, child abuse, and sexual assaults, but also encourages more awareness, outreach, and advocacy on Gender-based violence, sexual assaults, domestic violence, and child abuse which are taking place periodically. Finally, FPD maintains a database and information to study and analyze issues related to domestic violence which helps research and studies to combat the violence and stand united against gender inequality [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%